Environmental penalties and corporate carbon disclosure in China: divergent effects of resource availability and the role of social media pressure - Jing Shao; Wenjie Li; Lingtong Huang; Yuanhao Tian (Frontiers in Environmental Science)
IntroductionEnvironmental concerns and the escalating impacts of climate change have prompted governments to set ambitious carbon emission reduction targets. Corporations, as major contributors to carbon emissions, play a critical role in achieving these goals through transparent carbon disclosure. This study investigates the impact of environmental penalties on corporate carbon disclosure practices among Chinese-listed firms from 2009 to 2019, drawing on organizational legitimacy theory.MethodUsing data from publicly available corporate reports, we employed multivariate regression analysis to examine how environmental penalties influence carbon disclosure. Additionally, we explored the moderating roles of firms’ financial resource conditions and social media scrutiny.ResultThe results revealed that environmental penalties significantly enhance carbon disclosure, particularly in resource-redundant firms, while their effect diminishes in resource-constrained enterprises. Social media scrutiny amplifies the positive impact of penalties by increasing public pressure, highlighting the role of external stakeholders in fostering transparency.DiscussionThese findings underscore the importance of integrating tailored regulatory frameworks with active public and social media engagement to enhance corporate accountability and transparency. This study contributes to the literature on corporate social responsibility, offering actionable insights for policymakers, regulators, and corporate managers aiming to advance sustainability goals.